Design of Automated Rainout Shelter to Conduct Experiment on Drought Tolerant Maize Genotype - Shiva Kumar Jha; Mahendra Tripathi; Balram Bhandari; Bhanu Pokharel; Tika Karki; Keshab Babu Koirala (Journal La Multiapp, 2020)
Uneven and low precipitation areas of Nepal are continuously suffering from drought and received low productivity because of unavailability of suitable drought tolerant maize genotype. An attempt has been made first time in Nepal by constructing an automated rainout shelter with soil moisture based automated drip irrigation system at National Maize Research Program in 2018-2019 to conduct an experiment on drought tolerant maize genotype. The rainout shelters automatically covers the cropping area as soon as the rain sensor received a single drop of precipitation and also if the light intensity decreased to value set in the control panel. Likewise, the soil water level in different treatments were maintained on the basis of the treatment controlled with automatic drip irrigation system set to irrigate at threshold value set in the microcontroller. The complete system had found very useful in determining accurate amount of water required to cultivate drought tolerant maize genotype. We have tested drought tolerant variety RampurSo3Fo8 under 10 level of irrigation and it was determined that 495.2 mm of water is maximum level of water to produce highest yield of 3.32 t/ha whereas 445.6 mm to 247.6 mm of water could can be manage to produce competitive yield without any reduction. An experiment under such kind of infrastructure provide useful information on irrigation management practices required for drought variety in the natural environment. The research output also guides farmers and agriculturist in making Nepalese agricultural more sustainable, mechanized and productive.